A CGE analysis of the short-run welfare effects of tariff liberalisation in Uganda - Jennifer Mbabazi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
The promotion of human welfare is undoubtedly one of the greatest challenges of economic development. To achieve this, many developing countries adopted trade liberalisation in the late 1980s, premised on the theoretical evidence based on the definitive Heckscher-Ohlin theory which predicts gains for the poor. The empirical support for this theory, however, is at best mixed. This paper employs powerful Computable General Equilibrium techniques to data from Uganda, a typical Sub- Saharan Africa country largely recognized as a front-runner in trade liberalisation to investigate the short-run welfare impact of tariff liberalisation. It finds that trade liberalisation is no panacea to developing country problems. In fact, there are only minimal welfare gains largely accruing to the agricultural households. Furthermore, the importance of transfers (both government and inter-household) as well as exchange rate movements in determining differential welfare outcomes are highlighted.
Keywords: D58; I30; O55; 330; CGE modelling; tariff liberalisation; Uganda; Außenhandelsliberalisierung; Wohlfahrtseffekt; Allgemeines Gleichgewicht; Uganda